Halogen-free flame-retardant degradable polylactic acid composite material as well as preparation method and application thereof

By using calcium alginate modified carbon fiber and phosphoric acid modified chitosan as flame retardant filler in polylactic acid composite materials, the problems of flammability of polylactic acid and the toxicity of traditional flame retardants are solved, and the efficient flame retardant and good mechanical properties of non-halides are achieved, which is suitable for the preparation of flame retardant and degradable containers.

CN119823550AInactive Publication Date: 2025-04-15DALIAN TALENT GIFT CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510322165.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-19
Publication Date
2025-04-15
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The flammability of polylactic acid limits its application range, and traditional halogen-containing flame retardants are toxic and harmful, endangering personal health and the environment.

Method used

The non-halogen flame retardant degradable polylactic acid composite material is used to combine calcium alginate modified carbon fiber with phosphoric acid modified chitosan as flame retardant filler, and an appropriate amount of toughening agent and compatible agent are added to prepare the material by melt blending and molding treatment.

Benefits of technology

It achieves flame retardant properties without halides, is environmentally friendly, and has excellent flame retardant properties and good mechanical properties, and is suitable for the preparation of flame retardant and degradable containers.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention provides a halogen-free flame-retardant degradable polylactic acid composite material as well as a preparation method and application thereof, and belongs to the technical field of composite materials. The halogen-free flame-retardant degradable polylactic acid composite material provided by the invention is prepared from the following preparation raw materials in parts by mass: 80 to 100 parts of polylactic acid; 8-25 parts of a flame-retardant filler, wherein the flame-retardant filler comprises calcium alginate modified carbon fibers and phosphoric acid modified chitosan; 3-10 parts of a toughening agent; and 0.5-2 parts of a compatilizer. The calcium alginate modified carbon fiber and the phosphoric acid modified chitosan are compounded to serve as the flame-retardant filler, so that the flame-retardant effect is excellent; meanwhile, a proper amount of flexibilizer and compatilizer are adopted, so that the halogen-free flame-retardant degradable polylactic acid composite material has excellent flame retardant property and good mechanical property, and is suitable for preparing a flame-retardant degradable container.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of composite materials, and in particular to a non-halogen flame-retardant degradable polylactic acid composite material and a preparation method and application thereof. Background Art

[0002] Polylactic acid, also known as polylactide, is a polymer obtained by polymerization with lactic acid as the main raw material. The raw material source is sufficient and renewable. The production process of polylactic acid is pollution-free, and the product is biodegradable and can be recycled in nature. Therefore, it is an ideal green polymer material with broad application value in many fields such as electronic devices and biomedicine.

[0003] However, polylactic acid is flammable, which greatly limits its application scope. The use of flame retardants can improve the flame retardancy of polylactic acid and thus help expand its application scope. Although traditional halogen-containing flame retardants have good flame retardant properties, they will release some toxic and harmful gases during the application process, which will cause serious harm to human health and the environment. Summary of the invention

[0004] The object of the present invention is to provide a non-halogen flame retardant degradable polylactic acid composite material and a preparation method and application thereof. The non-halogen flame retardant degradable polylactic acid composite material provided by the present invention does not contain halides, is environmentally friendly, and has excellent flame retardant properties.

[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions: The present invention provides a non-halogen flame-retardant biodegradable polylactic acid composite material, which does not contain halides and comprises the following preparation raw materials by weight: Polylactic acid 80-100 parts; 8-25 parts of flame retardant filler, wherein the flame retardant filler comprises calcium alginate modified carbon fiber and phosphoric acid modified chitosan; 3~10 parts of toughening agent; Compatibilizer 0.5~2 parts.

[0006] Preferably, the mass ratio of the calcium alginate modified carbon fiber to the phosphoric acid modified chitosan is 1:0.5-1.5.

[0007] Preferably, the method for preparing the calcium alginate modified carbon fiber comprises the following steps: mixing carbon fiber, sodium alginate and water to obtain a mixed dispersion; The mixed dispersion is mixed with a soluble calcium salt and cross-linked to obtain the calcium alginate modified carbon fiber.

[0008] Preferably, the cross-linking treatment is carried out at a temperature of 20-35° C. and for a time of 10-40 min.

[0009] Preferably, the method for preparing the phosphoric acid-modified chitosan comprises the following steps: mixing chitosan, an organic acid reagent and water to obtain a chitosan solution; The chitosan solution is mixed with phosphoric acid for modification to obtain the phosphoric acid-modified chitosan.

[0010] Preferably, the modification treatment is carried out at a temperature of 40-70° C. and for a time of 3-10 hours.

[0011] Preferably, the toughening agent comprises polyetheretherketone and / or ethylene-1-octene copolymer.

[0012] Preferably, the compatibilizer comprises polyvinyl alcohol and / or maleic anhydride.

[0013] The present invention provides a method for preparing the non-halogen flame-retardant degradable polylactic acid composite material described in the above technical solution, comprising the following steps: The polylactic acid, flame retardant filler, toughening agent and compatibilizer are sequentially subjected to melt blending and molding treatment to obtain the non-halogen flame retardant degradable polylactic acid composite material.

[0014] The present invention provides the use of the non-halogen flame retardant and degradable polylactic acid composite material described in the above technical solution or the non-halogen flame retardant and degradable polylactic acid composite material prepared by the preparation method described in the above technical solution in a flame retardant and degradable container.

[0015] The present invention provides a non-halogen flame-retardant degradable polylactic acid composite material, which comprises the following raw materials by weight: 80-100 parts of polylactic acid; 8-25 parts of flame-retardant filler, wherein the flame-retardant filler comprises calcium alginate-modified carbon fiber and phosphoric acid-modified chitosan; 3-10 parts of toughening agent; and 0.5-2 parts of compatibilizer. The present invention adopts a compound of calcium alginate-modified carbon fiber and phosphoric acid-modified chitosan as flame-retardant filler, wherein the calcium alginate-modified carbon fiber is obtained by modifying carbon fiber by calcium alginate, and the phosphoric acid-modified chitosan is obtained by modifying chitosan by phosphoric acid, and the compound of the two has excellent flame-retardant effect; at the same time, the present invention adopts an appropriate amount of toughening agent and compatibilizer, which is conducive to ensuring that the non-halogen flame-retardant degradable polylactic acid composite material has excellent flame-retardant properties and good mechanical properties, and is suitable for preparing flame-retardant degradable containers. DETAILED DESCRIPTION

[0016] The present invention provides a non-halogen flame-retardant biodegradable polylactic acid composite material, which comprises the following raw materials by weight: Polylactic acid 80-100 parts; 8-25 parts of flame retardant filler, wherein the flame retardant filler comprises calcium alginate modified carbon fiber and phosphoric acid modified chitosan; 3~10 parts of toughening agent; Compatibilizer 0.5~2 parts.

[0017] The non-halogen flame retardant and degradable polylactic acid composite material provided by the present invention does not contain halides (specifically, it can be halogenated flame retardants), is environmentally friendly, and has excellent flame retardant properties. The non-halogen flame retardant and degradable polylactic acid composite material of the present invention is described in detail below.

[0018] In the present invention, unless otherwise specified, the raw materials used are commercially available products well known to those skilled in the art or are prepared by methods well known to those skilled in the art.

[0019] By weight, the raw materials for preparing the non-halogen flame-retardant degradable polylactic acid composite material of the present invention include 80 to 100 parts of polylactic acid, specifically 80 parts, 85 parts, 90 parts, 95 parts or 100 parts. As an embodiment of the present invention, the polylactic acid can be specifically poly-DL-lactic acid, and the weight average molecular weight of the poly-DL-lactic acid can be 100,000 to 400,000, specifically 100,000, 200,000, 300,000 or 400,000. In the embodiment of the present invention, the poly-DL-lactic acid with the above weight average molecular weight is used, which has good mechanical properties while ensuring good degradability.

[0020] Based on the mass fraction of the polylactic acid, the raw materials for preparing the non-halogen flame retardant degradable polylactic acid composite material of the present invention include 3 to 10 parts of toughening agent, specifically 3 parts, 4 parts, 5 parts, 6 parts, 7 parts, 8 parts, 9 parts or 10 parts. As an embodiment of the present invention, the toughening agent may include polyetheretherketone and / or ethylene-1-octene copolymer, specifically polyetheretherketone or ethylene-1-octene copolymer. The use of the above-mentioned types and amounts of toughening agents in the embodiments of the present invention is conducive to making the non-halogen flame retardant degradable polylactic acid composite material have better mechanical properties, especially when polyetheretherketone is used as a toughening agent, it is also conducive to improving the flame retardant properties of the non-halogen flame retardant degradable polylactic acid composite material.

[0021] Based on the mass fraction of the polylactic acid, the raw materials for preparing the non-halogen flame retardant degradable polylactic acid composite material of the present invention include 0.5 to 2 parts of a compatibilizer, specifically 0.5 parts, 0.8 parts, 1 parts, 1.2 parts, 1.5 parts, 1.8 parts or 2 parts. As an embodiment of the present invention, the compatibilizer may include polyvinyl alcohol and / or maleic anhydride, specifically polyvinyl alcohol or maleic anhydride. In the embodiment of the present invention, the compatibilizer of the above type and amount is used, so that each component has good compatibility, gives full play to the role of each component, and ensures that the non-halogen flame retardant degradable polylactic acid composite material has excellent flame retardant properties and mechanical properties.

[0022] Based on the mass fraction of the polylactic acid, the raw materials for preparing the non-halogen flame-retardant degradable polylactic acid composite material of the present invention include 8 to 25 parts of flame-retardant filler, specifically 8 parts, 10 parts, 12 parts, 14 parts, 16 parts, 18 parts, 20 parts, 22 parts or 25 parts. In the present invention, the flame-retardant filler includes calcium alginate modified carbon fiber and phosphoric acid modified chitosan; the calcium alginate modified carbon fiber is obtained by modifying carbon fiber with calcium alginate, and the phosphoric acid modified chitosan is obtained by modifying chitosan with phosphoric acid. The two flame-retardant fillers are used in combination to have excellent flame retardant properties, and are conducive to making the non-halogen flame-retardant degradable polylactic acid composite material have good mechanical properties. As an embodiment of the present invention, the particle size of the flame-retardant filler can be 0.2 to 3 mm, further can be 0.5 to 2 mm, and further can be 1 to 1.5 mm. As an embodiment of the present invention, the mass ratio of the calcium alginate modified carbon fiber to the phosphoric acid modified chitosan can be 1:0.5~1.5, specifically 1:0.5, 1:0.8, 1:1, 1:1.2 or 1:1.5. In the embodiment of the present invention, the mass ratio of the calcium alginate modified carbon fiber to the phosphoric acid modified chitosan is limited to the above range, which is conducive to giving full play to the synergistic effect of the two, and ensuring that the non-halogen flame retardant degradable polylactic acid composite material has excellent flame retardant properties and good mechanical properties.

[0023] As an embodiment of the present invention, the method for preparing the calcium alginate modified carbon fiber may include the following steps: mixing carbon fiber, sodium alginate and water to obtain a mixed dispersion; The mixed dispersion is mixed with a soluble calcium salt and cross-linked to obtain the calcium alginate modified carbon fiber.

[0024] The present invention mixes carbon fiber, sodium alginate and water to obtain a mixed dispersion. As an embodiment of the present invention, the concentration of the carbon fiber in the mixed dispersion can be 1-10wt%, specifically 1wt%, 2wt%, 3wt%, 4wt%, 5wt%, 6wt%, 7wt%, 8wt%, 9wt% or 10wt%; the mass of sodium alginate in the mixed dispersion is 10-50% of the mass of the carbon fiber, specifically 10%, 20%, 30%, 40% or 50%. The present invention does not specifically limit the mixing method, as long as the components can be fully mixed and uniform.

[0025] After obtaining the mixed dispersion, the present invention mixes the mixed dispersion with a soluble calcium salt for cross-linking treatment to obtain the calcium alginate modified carbon fiber. As one embodiment of the present invention, the soluble calcium salt can be specifically calcium chloride, and the mass ratio of the soluble calcium salt to sodium alginate can be 1:0.1~5, specifically 1:0.1, 1:0.3, 1:0.5, 1:1, 1:2, 1:3, 1:4 or 1:5. As one embodiment of the present invention, the soluble calcium salt can be specifically dissolved in water to form a soluble calcium salt solution, and then the soluble calcium salt solution is mixed with the mixed dispersion for cross-linking treatment; the concentration of the soluble calcium salt solution can be 5~20wt%, specifically 5wt%, 10wt%, 15wt% or 20wt%; the amount of the soluble calcium salt solution added is to ensure that the mass ratio of the soluble calcium salt to the sodium alginate is within the above requirements.

[0026] As an embodiment of the present invention, the temperature of the cross-linking treatment can be 20-35°C, specifically room temperature (25°C); the time can be 10-40, specifically 10min, 20min, 30min or 40min; the cross-linking treatment can be carried out under stirring conditions, and the present invention has no special restrictions on the stirring speed, as long as the cross-linking treatment is carried out smoothly. The present invention forms calcium alginate in situ on the surface of carbon fiber through cross-linking treatment, thereby obtaining calcium alginate modified carbon fiber, and the calcium alginate modified carbon fiber is compounded with phosphoric acid modified chitosan as a flame retardant filler, which can ensure that the obtained non-halogen flame retardant degradable polylactic acid composite material has excellent flame retardant properties and mechanical properties.

[0027] As an embodiment of the present invention, the cross-linking treatment may further include: solid-liquid separation of the liquid obtained after the cross-linking treatment, and drying the obtained solid material to obtain the calcium alginate modified carbon fiber; the solid-liquid separation method may specifically be filtration; the present invention has no special restrictions on the drying conditions, as long as sufficient drying can be achieved. As an embodiment of the present invention, when the particle size of the product obtained after drying does not meet the particle size requirements of the above-mentioned flame retardant filler, the drying may further include crushing or grinding, and the crushing or grinding conditions may ensure that the particle size requirements of the above-mentioned flame retardant filler are met, and the present invention has no special restrictions on this.

[0028] As an embodiment of the present invention, the method for preparing the phosphoric acid-modified chitosan may include the following steps: mixing chitosan, an organic acid reagent and water to obtain a chitosan solution; The chitosan solution is mixed with phosphoric acid for modification to obtain the phosphoric acid-modified chitosan.

[0029] The present invention mixes chitosan, an organic acid reagent and water to obtain a chitosan solution. As an embodiment of the present invention, the organic acid reagent can be formic acid and / or acetic acid, specifically acetic acid; the concentration of chitosan in the chitosan solution can be 5~15wt%, specifically 5wt%, 6wt%, 7wt%, 8wt%, 9wt%, 10wt%, 11wt%, 12wt%, 13wt%, 14wt% or 15wt%; the concentration of the organic acid reagent in the chitosan solution can be 1~3wt%, specifically 1wt%, 1.5wt%, 2wt%, 2.5wt% or 3wt%. The present invention does not specifically limit the mixing method, and can achieve sufficient mixing of the components.

[0030] After obtaining the chitosan solution, the present invention mixes the chitosan solution with phosphoric acid for modification treatment to obtain the phosphoric acid-modified chitosan. As an embodiment of the present invention, the concentration of the phosphoric acid can be 83~85wt%; the amount ratio of the chitosan to the phosphoric acid can be 1g:5~10mL, further can be 1g:6~9mL, and further can be 1g:7~8mL. As an embodiment of the present invention, the temperature of the modification treatment is 40~70℃, specifically 40℃, 45℃, 50℃, 55℃, 60℃, 65℃ or 70℃; the time is 3~10h, specifically 3h, 4h, 5h, 6h, 7h, 8h, 9h or 10h; the modification treatment can be carried out under stirring conditions, and the present invention has no special limitation on the stirring speed, and the modification treatment can be carried out smoothly. The present invention uses phosphoric acid to modify chitosan, and the obtained phosphoric acid-modified chitosan is compounded with calcium alginate-modified carbon fiber and used as a flame retardant filler, which can ensure that the obtained non-halogen flame retardant and degradable polylactic acid composite material has excellent flame retardant properties and mechanical properties.

[0031] As an embodiment of the present invention, the modification treatment may further include: mixing the modified treatment liquid obtained after the modification treatment with an alcohol reagent, and then subjecting the solid-liquid separation to washing and drying the obtained solid material in sequence to obtain the phosphoric acid-modified chitosan; the alcohol reagent may be ethanol, specifically anhydrous ethanol; the present invention has no special limitation on the amount of the alcohol reagent, as long as the phosphoric acid-modified chitosan is fully separated; the solid-liquid separation method may specifically be filtration; the reagent used for washing may be the above-mentioned alcohol reagent; the present invention has no special limitation on the drying conditions, as long as sufficient drying can be achieved. As an embodiment of the present invention, when the particle size of the product obtained after drying does not meet the particle size requirements of the above-mentioned flame retardant filler, the drying may further include crushing or grinding, and the crushing or grinding conditions may ensure that the particle size requirements of the above-mentioned flame retardant filler are met, and the present invention has no special limitation on this.

[0032] The present invention provides a method for preparing the non-halogen flame-retardant degradable polylactic acid composite material described in the above technical solution, comprising the following steps: The polylactic acid, flame retardant filler, toughening agent and compatibilizer are sequentially subjected to melt blending and molding treatment to obtain the non-halogen flame retardant degradable polylactic acid composite material.

[0033] As an embodiment of the present invention, the temperature of the melt blending can be 50-70°C, specifically 50°C, 55°C, 60°C, 65°C or 70°C; the time of the melt blending can be 15-40min, specifically 15min, 20min, 25min, 30min, 35min or 40min. In the embodiment of the present invention, the melt blending can be carried out in a mixer, and the speed of the mixer can be 80-100rpm, specifically 80rpm, 85rpm, 90rpm, 95rpm or 100rpm. The present invention does not specifically limit the method of the molding process, for example, it can be compression molding; the pressure of the compression molding can be 10-30MPa, specifically 10MPa, 13MPa, 15MPa, 18MPa, 20MPa, 23MPa, 25MPa, 28MPa or 30MPa; the time can be 1-15min, specifically 1min, 3min, 5min, 8min, 10min or 15min. The present invention has no special limitation on the size and shape of the mold used for the compression molding, which can be selected according to actual needs.

[0034] The present invention provides the use of the non-halogen flame retardant degradable polylactic acid composite material described in the above technical solution or the non-halogen flame retardant degradable polylactic acid composite material prepared by the preparation method described in the above technical solution in a flame retardant degradable container. The present invention does not specifically limit the specific size and shape of the flame retardant degradable container, and the appropriate size and shape can be selected according to actual needs.

[0035] The technical solutions in the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0036] Example 1 The carbon fiber, sodium alginate and water are mixed to obtain a mixed dispersion, wherein the concentration of the carbon fiber in the mixed dispersion is 6wt%, and the mass of the sodium alginate in the mixed dispersion is 40% of the mass of the carbon fiber; the mixed dispersion is mixed with a calcium chloride solution with a concentration of 15wt%, wherein the mass ratio of the sodium alginate to the soluble calcium salt is 1:1, and a cross-linking treatment is performed at room temperature and under stirring conditions for 20 minutes, and then the obtained feed liquid is filtered, and the filter cake is dried to obtain calcium alginate modified carbon fiber; Mix chitosan, acetic acid and water to obtain a chitosan solution, wherein the concentration of chitosan in the chitosan solution is 12wt% and the concentration of acetic acid is 2.5wt%; mix the chitosan solution with phosphoric acid with a concentration of 85wt%, wherein the amount ratio of chitosan to phosphoric acid is 1g:7mL, perform modification treatment at 55°C with stirring for 6h, then mix the obtained feed liquid with anhydrous ethanol, precipitate is precipitated, filter, wash the obtained filter cake with anhydrous ethanol, and then dry to obtain phosphoric acid-modified chitosan; By mass, 90 parts of polylactic acid (specifically poly DL-lactic acid, with a weight average molecular weight of 200,000), 12 parts of flame retardant filler (calcium alginate modified carbon fiber and phosphoric acid modified chitosan are compounded in a mass ratio of 1:1, with a particle size of 1-1.5 mm), 6 parts of toughening agent (specifically polyetheretherketone) and 1.2 parts of compatibilizer (specifically maleic anhydride) are placed in a mixer, melt-blended for 25 minutes at a temperature of 65°C and a rotation speed of 85 rpm, the resulting blend is placed in a mold, and compression molded at 13 MPa for 5 minutes to obtain a non-halogen flame retardant and degradable polylactic acid composite material.

[0037] Examples 2 to 7 and Comparative Examples 1 to 4 The degradable polylactic acid composite material was prepared by referring to the method of Example 1, except that the formula was different, as shown in Table 1.

[0038] Table 1 Formulas of degradable polylactic acid composite materials in various examples and comparative examples

[0039] Test Example 1 The performance tests were conducted on the degradable polylactic acid composite materials in each embodiment and the comparative example, wherein the limiting oxygen index (LOI) was tested according to the method in GB / T2406-2008, the flammability level was tested according to the flame retardant level UL 94 test standard, and the tensile strength was tested according to the method in GB / T 1040-2006. The specific test results are shown in Table 2. As can be seen from Table 2, the present invention uses a compound of calcium alginate modified carbon fiber and phosphoric acid modified chitosan as flame retardant fillers, and uses an appropriate amount of toughening agent and compatibilizer, which is conducive to ensuring that the non-halogen flame retardant degradable polylactic acid composite material has excellent flame retardant properties and good mechanical properties.

[0040] Table 2 Performance test results of the degradable polylactic acid composite materials in various embodiments and comparative examples

[0041] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A non-halogen flame-retardant biodegradable polylactic acid composite material, comprising the following raw materials by weight: Polylactic acid 80-100 parts; 8-25 parts of flame retardant filler, wherein the flame retardant filler comprises calcium alginate modified carbon fiber and phosphoric acid modified chitosan; 3~10 parts of toughening agent; Compatibilizer 0.5~2 parts.

2. The non-halogen flame-retardant biodegradable polylactic acid composite material according to claim 1, characterized in that: The mass ratio of the calcium alginate modified carbon fiber to the phosphoric acid modified chitosan is 1:0.5-1.

5.

3. The non-halogen flame-retardant biodegradable polylactic acid composite material according to claim 1 or 2, characterized in that: The preparation method of the calcium alginate modified carbon fiber comprises the following steps: mixing carbon fiber, sodium alginate and water to obtain a mixed dispersion; The mixed dispersion is mixed with a soluble calcium salt and cross-linked to obtain the calcium alginate modified carbon fiber.

4. The non-halogen flame-retardant biodegradable polylactic acid composite material according to claim 3, characterized in that: The temperature of the cross-linking treatment is 20-35° C., and the time is 10-40 minutes.

5. The non-halogen flame-retardant biodegradable polylactic acid composite material according to claim 1 or 2, characterized in that: The preparation method of the phosphoric acid-modified chitosan comprises the following steps: The chitosan solution is mixed with phosphoric acid for modification to obtain the phosphoric acid-modified chitosan.

6. The non-halogen flame-retardant biodegradable polylactic acid composite material according to claim 5, characterized in that: The temperature of the modification treatment is 40-70° C. and the time is 3-10 hours.

7. The non-halogen flame-retardant biodegradable polylactic acid composite material according to claim 1 or 2, characterized in that: The toughening agent includes polyetheretherketone and / or ethylene-1-octene copolymer.

8. The non-halogen flame-retardant biodegradable polylactic acid composite material according to claim 1 or 2, characterized in that: The compatibilizer includes polyvinyl alcohol and / or maleic anhydride.

9. The method for preparing the non-halogen flame-retardant degradable polylactic acid composite material according to any one of claims 1 to 8, comprising the following steps: The polylactic acid, flame retardant filler, toughening agent and compatibilizer are sequentially subjected to melt blending and molding treatment to obtain the non-halogen flame retardant degradable polylactic acid composite material.

10. Use of the non-halogen flame retardant and degradable polylactic acid composite material according to any one of claims 1 to 8 or the non-halogen flame retardant and degradable polylactic acid composite material prepared by the preparation method according to claim 9 in flame retardant and degradable containers.

Citation Information

Patent Citations

  • Intumescent high-efficiency composite fire retardant, and preparation method thereof

    CN110498952A

  • Antibacterial flame-retardant polyester fiber master batch, fiber and preparation method of antibacterial flame-retardant polyester fiber master batch

    CN117364263A

  • Biodegradable plastic product reinforcing material and preparation method thereof

    CN118580655A

  • Preparation method and application of flame-retardant polypropylene material

    CN119286126A